Bacterial Pathogenesis and Antibacterial Control 2018
DOI: 10.5772/intechopen.72110
|View full text |Cite
|
Sign up to set email alerts
|

Are Herbal Products an Alternative to Antibiotics?

Abstract: Medicinal plants have been widely used in the management of infectious diseases and by now, many of the ancient remedies have proven their value through scientific methodologies. Although the mechanisms underlying most plant-derived remedies are not well understood, the success of herbal medicine in curing infectious diseases shows that many plants have beneficial effects in various bacterial, fungal, viral or parasitic infections. The modern methodologies in the isolation, purification and characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Thus, organic and conventional poultry production requires alternative strategies to enhance poultry growth and performance ( Diaz-Sanchez et al., 2015 ). Herbs, spices, and various other natural plant compounds are being assessed as effective alternatives to antibiotics and approximately do have promoting growth effects, antibacterial properties, and other health-related advantages ( Ionescu, 2017 ; Al-Sagheer et al., 2019 ; Abou-Elkhair et al., 2020 ; Naiel et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organic and conventional poultry production requires alternative strategies to enhance poultry growth and performance ( Diaz-Sanchez et al., 2015 ). Herbs, spices, and various other natural plant compounds are being assessed as effective alternatives to antibiotics and approximately do have promoting growth effects, antibacterial properties, and other health-related advantages ( Ionescu, 2017 ; Al-Sagheer et al., 2019 ; Abou-Elkhair et al., 2020 ; Naiel et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…). This compound was considered the primary treatment for malaria for quite a long time, although alternative plant-based active chemicals have now proven their worth [2]. Additionally, numerous investigations have indicated that quinine exhibits antibacterial effects.…”
Section: Curcuminmentioning
confidence: 99%
“…Numerous fundamental oils incorporate (ethyl-dimethyl-(3-sulfopropyl)azanium) (C 7 H 18 NO 3 S + ) (PubChem CID 448830, for example, E. globulus (eucalyptus) oil, Melaleuca alternifolia (tea tree) oil, or R. officinalis oil (rosemary). It is one of the fundamental unique combinations in key oils, which clarifies their antibacterial properties [ 2 ]. It functions as an accelerator of penetration for topical application to the skin [ 16 ].…”
Section: Active Compounds From Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contemplating action for the observed scenario demands our sincere focus towards the use of alternative remedies in combating antimicrobial resistance. Verily, many published studies report the potential of plant extracts as a possible alternative to antibiotics [8,9,10]. However, comparatively few documented records including research publications report the efficiency of plant extracts in treatment of infections caused by multi drug resistant pathogens [11,12].…”
Section: Introductionmentioning
confidence: 99%